2020
DOI: 10.3892/ol.2020.12021
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑23b‑3p promotes pancreatic cancer cell tumorigenesis and metastasis via the JAK/PI3K and Akt/NF‑κB signaling pathways

Abstract: MicroRNA (miR)-23b-3p plays an important role in tumor growth, proliferation, invasion and migration in pancreatic cancer (PC). However, the function and mechanistic role of miR-23b-3p in the development of PC remains largely unknown. In the present study, the miR-23b-3p levels in the serum of patients with PC were found to be elevated, and the phosphorylation levels of Janus kinase (JAK)2, PI3K, Akt and NF-κВ were found to be upregulated. In addition, miR-23b-3p was induced in response to interleukin-6 (IL-6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Consistent with the results of these aforementioned studies, the findings of the current study revealed that miR-23b-3p expression was downregulated in CRC tissues. However, other studies have reported that miR-23b-3p expression is upregulated in several types of malignant tumor, including renal ( 28 ), lung ( 29 ) and pancreatic cancer ( 30 , 31 ). The discrepancy in these results may be due to differences in both the tissue types and the disease in question.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the results of these aforementioned studies, the findings of the current study revealed that miR-23b-3p expression was downregulated in CRC tissues. However, other studies have reported that miR-23b-3p expression is upregulated in several types of malignant tumor, including renal ( 28 ), lung ( 29 ) and pancreatic cancer ( 30 , 31 ). The discrepancy in these results may be due to differences in both the tissue types and the disease in question.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with these studies, we observed the down-regulation of miR-23b-3p in CRC tissues. However, some scholars have been reported that up-regulation of miR-23b-3p in several types of malignant tumors, including pancreatic cancer [39], renal cancer [40], lung cancer [41] and pancreatic cancer [42]. The discrepant results may be due to the different tissues or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The Akt/NF- κ B-associated signaling pathways were promoted by mRNAs, microRNA (miRNAs), and lncRNAs in pancreatic cancers. Other studies showed that the Akt/NF- κ B signaling pathway was promoted by CCN1 [ 34 ] and miRNA-23b-3p [ 35 ] and involved in the tumorigenicity of pancreatic cancer. Our present study suggests that the NK-1R/Akt/NF- κ B signaling system affecting PNI might be a novel target for pancreatic cancer therapy.…”
Section: Discussionmentioning
confidence: 99%